Factors Associated with Attrition of Girls Students from School in Bangladesh (Journal of Scientific Research, 2020)
Many girls who enrolled in a school but didn’t complete elementary or secondary education, have become a serious problem in the last few decades in Bangladesh. Several studies have been conducted to identify the determinants of school dropout by constructing bivariate and multiple logistic regression (MLR) model. Bangladesh multiple indicator cluster surveys (MICS) 2012 data were selected in this investigation. This study was based on girls aged between 15 and 17 years since all these girls should have been in school or have completed primary education. The backward stepwise method was used for model selection and fitting to the dataset. From 4800 girls, 29.1% were out of school and 70.9% were attending school. Backward stepwise method confirmed that girl’s marital status, area, division, wealth index, religion, mothers and father’s aliveness and household education were the major reasons of girl’s dropout and these covariates are only considered in the analysis. The MLR analysis showed that married girls were significantly (OR 11.06; 95% CI 9.05–13.56) more likely to attrition compared to unmarried girls. School-based programs aimed at preventing child marriage should target girls from the fifth grade because of their escalated risk, and they need to prioritize girls from disadvantaged groups.